An Output-oriented Approach to the Impact of Online Written Languaging on Form-Focused Writing Tasks - Natasha Pourdana (National Research University Higher School of Economics, 2023)
Background. Despite the growing interest of second language acquisition (SLA) researchers in the languaging process, a few studies have been done on its dynamic attributes in various writing tasks. Purpose. This study investigated how online written languaging (WL) might impact English-as-a-Foreign-Language (EFL) learners' performance on form-focused writing tasks with production-based and comprehension-based output orientation in Google Docs, and how the output orientation of form-focused writing tasks could determine the WL attributes of quantity and focus. Methods. To do so, 112 Iranian EFL university students were selected and assigned to four parallel groups. In an eight-week experiment, two groups worked on gap-filling tasks (production-based) and two groups on error-identification tasks (comprehension-based) in parallel ±WL conditions. Results. Statistical analysis indicated a significant interaction between task output orientation and WL production. So, on both production-based and comprehension-based tasks, the +WL groups outperformed the ˗WL groups. Moreover, in the +WL condition, the task output orientation determined the quantity of WL episodes, but not their focus on grammar (G-WL) and lexis (L-WL) in production-based and comprehension-based tasks. As such, the +WL group who completed the production-based tasks produced much more WL episodes than the +WL group who completed the comprehension-based tasks. Yet, both groups equally produced more L-WL episodes than G-WL episodes. Сonclusion. The study had several implications for language teachers to maximize learning opportunities by teaching how to language in various writing tasks on online platforms. The L2 teachers are also recommended to adopt an alternative approach to translation as a form-focused writing task.